Old Polish Sources of Romantic Picture of Podole (Selected Examples) - Ryba, Renata (Colloquia Litteraria, 2018)
The article considers romantic preoccupations with the traditions of the Polish Republic of Nobles. The author indicates how the Romanticism authors reached out to the history of Podolia and how literary images of Podolia are rooted in texts from older periods. She never points to individual Old-Polish texts quoted by nineteenth-century authors; she highlights, instead, how Old-Polish literature dealing with Podolia and certain anti-Turkish texts inspired Romantic authors in general. The author pays particular attention to selected motifs from Old-Polish literature that used to be employed in Romantic texts to create historical image of Podolia; among these one can distinguish such motifs as the utility of Podolian lush nature, Turkish captivity (“jasyr”), Polish-Lithuanian Eastern borderlands knight, and the soil that is fecund yet scorched by war. The article discusses sixteenth- and seventeenth-century authors, including Bartosz Paprocki, Piotr Gorczyn, and Marcin Paszkowski as well as Romantic writers such as Maurycy Gosławski, Tymon Zaborowski, and Seweryn Groza.